Coordination-modulated piezochromism in metal-viologen materials - Sui, Qi; Yuan, Ye; Yang, Ning-Ning; Li, Xin; Gong, Teng; Gao, En-Qing; Wang, Lin (Journal of materials chemistry. C, Materials for optical and electronic devices, 2017)
While stimuli-responsive chromic phenomena are well known for various viologen-containing organic and metal-organic materials, viologen-based piezochromism is a very recent discovery in organic compounds. Here we present the first piezochromic metal-viologen material and the modulation of the pressure-responsive behavior through coordination structures. By means of ultraviolet-visible spectroscopy, X-ray photoelectron spectroscopy, electron paramagnetic resonance, in situ / ex situ X-ray diffraction and DFT calculations, we demonstrated that a zigzag-chain Cd II coordination polymer ( 1 ) with a viologen-dicarboxylate zwitterionic ligand shows reversible piezochromism, with modulations in threshold pressure and visible-light absorption (color) compared with the free ligand. We also illustrated that piezochromism can be suppressed upon coordination of the same ligand in a rigid 3D framework with the same metal ion. Two basic requirements were proposed from viologen-based piezochromism: appropriate donor-acceptor contacts providing electron transfer pathways, and structural flexibility allowing pressure to further reduce the contacts. We expect great prospects in tuning piezochromism and designing new pressure-responsive materials through diverse metal-viologen combinations. The very fast photochromic response of compound 1 at ambient pressure was also studied, which was attributed to the rather short donor-acceptor contacts in the structure. The first reversible piezochromic metal-viologen material, via electron transfer, and the modulation of the pressure-responsive behavior through coordination structures are presented. The very fast photochromic response of the material at ambient pressure is also studied.